Hazel plantation planning using GIS and multicriteria decision analysis - Plaščak, Ivan (Array, 2019)
Spatial and environmental conditions on the agricultural land are invariable components and any plantation planning should take them into consideration. The conducted research presented methodology for suitability calculation of hazel plantations based on multicriteria analysis, performed in Vukovar-Srijem County. Nine criteria representing topographic, climate, pedology and infrastructure properties were modelled in GIS environment. Values of created layers were standardized using stepwise standardization and their respective weights were calculated by Analytical Hierarchical Process. These values were integrated using weighted linear combination, resulting with suitability values. The surrounding area of the City of Ilok had the highest suitability for hazel plantation in the studied locality, with maximum suitability 4.1 out of 5.0. Suitability was visualized on a thematic map, which enables farmers to interpret the data.